1996
DOI: 10.1029/95jd01700
|View full text |Cite
|
Sign up to set email alerts
|

Validation of mesosphere and lower thermosphere winds from the high resolution Doppler imager on UARS

Abstract: Horizontal wind fields in the mesosphere and lower thermosphere are obtained with the high resolution Doppler imager (HRDI) on the Upper Atmosphere Research Satellite (UARS) by observing the Doppler shifts of emission lines in the 09. atmospheric band. The validity of the derived winds depends on an accurate knowledge of the positions on the detector of the observed lines in the absence of a wind-induced Doppler shift. Relative changes in these positions are readily identified in the routine measurements of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 52 publications
15
116
1
Order By: Relevance
“…The height resolutions, estimated at ∼ 20 km in winter and ∼ 16 km in summer from the AVK FWHMs, are coarser than for the O 3 wind retrievals whereas the observation errors are smaller at ∼ 3 m s −1 in both winter and summer conditions at Halley. Our simulated wind retrieval is comparable to the polar mesospheric wind speeds above the South Pole determined with uncertainty ± 5 m s −1 by observing the CO line at 461 GHz (Burrows et al, 2007).…”
Section: Choice Of Emission Line(s)supporting
confidence: 80%
See 2 more Smart Citations
“…The height resolutions, estimated at ∼ 20 km in winter and ∼ 16 km in summer from the AVK FWHMs, are coarser than for the O 3 wind retrievals whereas the observation errors are smaller at ∼ 3 m s −1 in both winter and summer conditions at Halley. Our simulated wind retrieval is comparable to the polar mesospheric wind speeds above the South Pole determined with uncertainty ± 5 m s −1 by observing the CO line at 461 GHz (Burrows et al, 2007).…”
Section: Choice Of Emission Line(s)supporting
confidence: 80%
“…Le Pichon et al, 2010;Assink et al, 2012Assink et al, , 2013Chunchuzov et al, 2015). Over a 14-year period the space-borne high-resolution Doppler imager (HRDI) (Burrage et al, 1996) measured wind velocities typically between 60 • N and 60 • S and down to 50 km and contributed to the Upper Atmosphere Research Satellite (UARS) Reference Atmosphere Project (URAP) (Swinbank and Ortland, 2003) wind climatology. Also on UARS, the limb-sounding WIND Imaging Interferometer (WINDII) observed O( 1 S) airglow emission to measure winds over 90-110 km (Gault et al, 1996b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burrage et al (1996) concluded that the HDRI results were more consistent with falling sphere measurements and with WINDII measurements and so by inference that MF wind magnitudes were too small. It is worth noting that the HRDI measurements represented averages over several hundred kilometers in the meridional direction.…”
Section: Satellite Intercomparisonssupporting
confidence: 50%
“…Intercomparisons between HRDI and a number of MF/HF SA FCA radars found that mean and tidal component winds in the satellite instrument were larger than the corresponding radar winds (e.g., Khattatov et al 1996), and Burrage et al (1996) concluded that HRDI measured larger winds than MF radars, but that the size of the difference varied from radar to radar. Burrage et al (1996) concluded that the HDRI results were more consistent with falling sphere measurements and with WINDII measurements and so by inference that MF wind magnitudes were too small.…”
Section: Satellite Intercomparisonsmentioning
confidence: 99%